Boas práticas de fabricação de insumos de origem vegetal: evolução das normas que norteiam a produção e o panorama do parque fabril brasileiro - Branco, Patrícia Francisco (2015)
The aim of this work is to show the panorama of the manufacturing industries of herbal active ingredient supplies in Brazil. In this analysis we considered the evolution of standards relating to Good Manufacturing Practices (GMP) of Plant Origin Inputs, that occurred according to herbal records updates and existing pharmaceutical ingredients in Brazil. These changes were due to the publishing of the National Policy of Medicinal Plants and Herbal medicines in 2006. Brazilian legislations were analyzed and identified the current situation of the manufacturing industries in Brazil through the system, or database Registration of Pharmaceutical Drugs assets, inserted in DATAVISA system. A small number of manufacturers of these inputs have been observed and most companies are international, while Brazilian companies are at different stages of compliance with the GMP standards. This scenario demonstrates the real need for manufacturers to adapt to current regulations, such as the standardization of health surveillance, as well as the creation of an effective monitoring system of the Brazilian Industries by the National Health Surveillance System. This report is also a detailed guide on how to fill out the inspection report for herbal active ingredient manufactures.